Teachers' Attitudes towards Webinars in Professional Development: A Case Study at Secondary School in Indonesia - Adi Budi Perkasa; Surono Surono (Yayasan Keluarga Guru Mandiri, 2023)
The pandemic has prompted the proliferation of webinars for professional development in the teaching profession. This case study investigates the teachers' attitudes toward the webinars as professional development. The participants were the teachers from a junior high school in one public school in Indonesia. The researchers selected three participants based on the questionnaire by considering the frequencies following the webinars. The researchers conducted semi-structured interviews by adapting the three components of an attitude referring to behaviour, cognition, and affective. The study is significant to investigate how teachers perceive webinars as a tool for their professional development, describe the impacts, and as input for the educational organisation in conducting teachers' training. The results revealed the teachers’ positive attitudes regarding behaviours, beliefs, and feelings towards the webinar as professional development. A webinar has eliminated the time and geographical boundaries in conducting professional development. Moreover, more professional networking and opportunities are additional advantages that bring more engagement and exposure to continuing their professional development. This research advocates that more webinars be held to develop the teachers' professionalism by related institutions and to open more access to growing teachers' careers by considering appropriate material and time based on the teachers' needs.